2013
DOI: 10.4236/jwarp.2013.512119
|View full text |Cite
|
Sign up to set email alerts
|

Germicidal Action of Some Metals/Metal Ions in Combating <i>E. coli</i> Bacteria in Relation to Their Electro-Chemical Properties

Abstract: The germicidal properties of some metals and metal compounds were investigated in relation to their electro-chemical properties that may play a role in the inactivation of E. coli bacteria. These properties included the atomic and ionic radii, ionization energy, oxidation state, energy of formation with hydro-sulfide groups, and the redox potential of the metals. Cultures of E. coli bacteria with predetermined numbers of colony-forming units (CFU's) were brought in contact with the metals as well as metal comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Recent studies showing that non-indole-producing bacteria generate various oxygenases which may degrade indole or interfere with indole signaling [ 56 , 57 ]. Many oxygenase and reductase reactions may be involved in metal ion facilitation in bacteria [ 58 ]. The ability of S. oneidensis to reduce oxidized metals or nitrate effectively has been identified as an important intrinsic activity of Shewanella species [ 59 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showing that non-indole-producing bacteria generate various oxygenases which may degrade indole or interfere with indole signaling [ 56 , 57 ]. Many oxygenase and reductase reactions may be involved in metal ion facilitation in bacteria [ 58 ]. The ability of S. oneidensis to reduce oxidized metals or nitrate effectively has been identified as an important intrinsic activity of Shewanella species [ 59 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In disinfection systems that contain both copper and silver, copper ions permeate the cell wall, opening a pathway for silver ions to permeate into the microorganisms. The binding of the silver ions to the cell's proteins, respiratory enzymes, DNA, and RNA causes the cell's entire life support system to become immobilized (Lenntech, 2010).According to a recent study on copper surfaces showed that hydroxyl radicals in the solution are responsible for microbes fatal action (Oyanedel et al, 2008;Santo et al, 2011. This method is typically employed in large-scale, commercial water disinfection systems where metal ions are produced chemically or electrolytically, and it has been found to be extremely successful (Varkey, 2010). The fact that electrolytic systems require a power source in order to function is a drawback (Mehtar et al, 2008).…”
Section: Original Articlementioning
confidence: 99%
“…In contrast, the biocidal efficiency of latex films with MgO nanoparticles can be explained by the high alkalinity of the coating film (see pH data in Table 2), which creates an unfavourable environment for MOs and, in addition, increases the activity of reactive oxygen species [83]. It should be emphasized here that the exact antimicrobial mechanism of MeO nanoparticles has not yet been clearly elucidated, but lipid peroxidation, the formation of reactive oxygen species, the presence of metal cations destroying MO enzymes, or the internalization of nanoparticles have been assumed [117][118][119][120]. It is further hypothesized that when metal cations enter a bacterial cell, the DNA molecule changes to a condensed form and loses its ability to replicate, leading to cell death [121,122].…”
Section: Antimicrobial Properties Of Coating Filmsmentioning
confidence: 99%